The distribution and morphology of microplastics in coastal soils adjacent to the Bohai Sea and the Yellow Sea - Zhou, Qian; Zhang, Haibo; Fu, Chuancheng; Zhou, Yang; Dai, Zhenfei; Li, Yuan; Tu, Chen; Luo, Yongming (Geoderma, 2018)
Microplastics (<5 mm) are considered to be emerging pollutants of global concern. Investigations on microplastics pollution in coastal and marine environments have increased recently but knowledge gaps still exist regarding microplastics in coastal beach soils with high-intensity human activities. In the present study a total of 120 soil samples were taken from 53 sites along >3000 km of coastline in Shandong province, east China, adjacent to both the Bohai Sea and the Yellow Sea coastlines under different land use management. Microplastics were separated from the soil samples using a continuous flow and floating separation apparatus. The shape type, size, abundance, spatial distribution, polymer composition and surface morphology of the microplastics were identified by a range of advanced microscopic and micro-analytical methods. The analytical results show that seven shape types, namely foams, pellets, fragments, flakes, fibers, films and sponges, were present in the beach soils. The polymer composition of the microplastics included polyethylene, polypropylene, polystyrene, polyether urethane and a polymer blend of both polyethylene and polypropylene. Approximately 60% of the observed microplastics had a size range < 1 mm. Microplastic abundance varied greatly among the soils, ranging from 1.3 to 14,712.5 N kg−1 (dry weight) as influenced by high-intensity human activities such as mariculture, tourism, and port construction. The seven shape types of microplastics from the coastal environment had different weathering surface morphologies, showing scratches, creases, micropores, cracks, either concave or convex, and of various shapes and sizes, possibly due to physical friction, photochemical oxidation and/or animal attack. Algae or crude oil was observed on the surface of some microplastics. The weathered surfaces of microplastics might act as a high-capacity carrier with adhering microorganisms and chemicals. Further studies are required on the weathering processes, sorption capacity and transport of microplastics especially in smaller size (<1 mm) under coastal conditions. •Comprehensive study on microplastics in coastal soils as influenced by human activities.•Different beaches showed different levels of microplastic contamination.•Flakes and white foams dominated the microplastics in the study area.•Surface morphology of microplastics showed deep weathering in the beaches.